Evaluación del rendimiento inicial de la planta de tratamiento de aguas residuales Las Esclusas - Macías Suárez, Pedro Abraham (2023)
The study focused on evaluating the initial performance of the Wastewater Treatment Plant (WWTP) Las Esclusas by collecting water samples and assessing key indicators such as Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) in soluble and particulate form. The jar test technique was used to determine the most efficient dosages of ferric chloride and cationic polymer that would achieve proper removal of contaminants. The results showed that the combination of 25% ferric chloride with 1% cationic polymer was optimal, resulting in rapid agglomeration and sedimentation of floculated particles. This dosage demonstrated high efficiency in removing BOD and COD, complying with current environmental standards. WWTP Las Esclusas successfully met the established discharge limits, ensuring adequate treatment of wastewater before being discharged into the environment. The combination of ferric chloride and cationic polymer is presented as a recommended and sustainable alternative for wastewater treatment in Guayaquil, contributing to responsible management and environmental protection. In summary, the study provided satisfactory results that defined an optimal dosage to improve treatment efficiency and ensure clean and safe water for the community. This work laid important foundations for future advancements in wastewater treatment, contributing to scientific and technical development in this field.